TREATMENT OPTION WITH DENTAL IMPLANTS IN PATIENTS WITH HYPODONTIA - peeva Petreska, Marija; Veleska stevkovska, Daniela (Medicinski časopis, 2013)
TREATMENT OPTION WITH DENTAL IMPLANTS IN PATIENTS WITH HYPODONTIA Abstract Hypodontia in the permanent dentition is a significant clinical challenge, particularly in the treatment of adolescent patients who are missing anterior teeth. They have severe aesthetic and psychological disorders and satisfying the aesthetic moment is the main motivation for treatment, but the goal in the management of hypodontia for the therapist is not only to improve the aesthetics but also to accomplish a good masticatory function with long lasting and predictable results. The selection of an appropriate therapeutic option, needs multidisciplinary approach and team coordination, first during treatment planning and then for determining the most appropriate time and method for subsequent orthodontic, surgical and prosthetic treatment. The aim of the authors is through the presentation of clinical material with hypodontia of the lateral incisors in maxilla and mandible, to show the need of multidisciplinary approach in the treatment of hypodontia using dental implants in the aesthetic region, and to emphasize the critical moments of the surgical aspects in order to achieve the best aesthetic and functional outcome. Good cooperation with the patients and their family is of particular importance, especially because of the long interval of orthodontic and surgical treatment until the final results are achieved. Key words: hypodontia, dental implants, surgical aspects, orthodontic therapy